Perancangan Buku Cerita Bergambar Tentang Sikap Anak Terhadap Tindak Kekerasan Orang Tua Sebagai Media Edukasi Anak - Indonesia, Gianluca Lancana; Budiardjo, Hardman; Yosep, Sigit Prayitno (Jurnal Art Nouveau, 2017)
Every parents has their own way to lecture their children. But because they feel like their children is theirs solely, some parents apply their policies as their wishes despite how much the intensities. Sometimes the harsh acts turns into child abuses in home. Child abuse is still happening and even increasing every year. Other than wrong way of parent’s lecturing, child abuse sometimes happens because of parent’s impingement even though campaign of children’s rights often provided by many institutions in Indonesia. Child abuses can affect children’s growth in the future. Some cases even gives children trauma, making them passive or even worse, becomes rebellious. This research will provide a friendly learning media for children to anticipate so they know how to behave  when they see things in reality. The learning media will be made in children story book so they have image about unusual acts in home. Research will use David McClelland’s theory, n-Ach, so children have motivation to be a successful person in term of being positive when meet the conditions. Keywords: Child Abuse, Children Story Book